Terengganu Malay Dialect Control in Teaching and Learning the Dikir Barat Credited Co-curiculum based Education among University Students in Malaysia Terengganu - Musa, Azlina (International Journal of Psychosocial Rehabilitation, 2020)
This paper will discuss the control of the Terengganu Malay dialect in teaching and learning dikir barat credited to co-curriculum-based education among students of University Malaysia Terengganu in Kuala Nerus, Terengganu. Each student is placed at University Malaysia Terengganu within a specific study group come from diverse backgrounds and different regions or nation states that are not so efficient control of Terengganu Malay dialect. This paper will identify problem students in mastering the vocal sound of the Terengganu Malay dialect. Accordingly, this paper will examine to what extent the effectiveness of a student’s ability to master the language of dikir barat and chanting fluency and the Terengganu Malay dialect. In addition, the success of research is the subject of dikir barat, which can help students cultivate their lives in an atmosphere of learning environments that is completely surrounded by a community speaking in the Terengganu Malay dialect in their daily lives. Thus, students who have migrated to the state of Terengganu should master the language, develop their understanding, and develop their ability to use the Terengganu dialect as one of the communication tools to facilitate daily interaction and create a harmonious relationship. The study also identifies the level of skills among the students who speak non-Malay in the Malay dialect of Terengganu in performances. Besides teaching and learning the Terengganu Malay dialect in the organization of shows due to the chanting and entertainment while in the classroom, it is a uniqueness of the credited co-curriculum-based education. It is also an attempt to preserve the heritage of the local language variation within the context of the Terengganu language usage. The discussion was based on observation, interview, recording and questionnaire findings with fifty students who had enrolled in dikir barat subjects in credit curriculum education. Re-documenting this study may add further sources of reference to other researchers in the future. It can also reinforce the language, culture, and society around it.